The effect of virtual reality on isometric muscle strength - ÇAMLIGÜNEY, ASİYE FİLİZ (My University, 2022)
© 2022 Mattioli 1885. All rights reserved.The aim of the study is to determine the acute effects of virtual reality on isometric muscle strength, pain intensity, perceived exertion, and heart rate. The study sample comprised 46 male sedentary individuals with a mean age of 28,56±5,25, who don’t have a sports experience and any health problems. Participants were divided into two groups, A and B, and grouped randomly. The mean age of group A is 29,00±6,13 years, height 170,78±7,51 cm, body weight 70,58±9,57 kg. The mean age of group B is 27,69±3,94 years, height 172,69±6,32 cm, body weight 69,57±8,65 kg. During the Wall Squat Test, the participants verbally informed the perceived pain intensity and perceived exertion level every 30 seconds, and the heart rate was monitored using a smartwatch. After the first measurements were completed, a break was given for one week, and then a cross matching was made. According to the results of the study; It was determined that groups using virtual reality were more advantageous after first measurement and cross matching. Group virtual reality performed higher during the Wall Squat Test, and it was also determined that the pain intensity and perceived exertion levels were lower during the test. However, there was no significant difference in heart rate between the groups.
Keywords: Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Sağlık Bilimleri; Mühendislik ve Teknoloji; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Food Engineering; Health Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Tarım Bilimleri; BESLENME VE DİYETETİK; GIDA BİLİMİ VE TEKNOLOJİSİ; Agriculture & Environment Sciences (AGE); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; FOOD SCIENCE & TECHNOLOGY; Yemek bilimi; Yaşam Bilimleri; Beslenme ve Diyetetik; Food Science; Life Sciences; wall squat; pain intensity; perceived exertion; heart rate; PAIN-CONTROL; EXERCISE; ANXIETY; DISTRACTION; EXPECTANCY; EXPERIENCE; BENEFITS; THERAPY; ADULTS; MOOD; wall squat; pain intensity; perceived exertion; heart rate.